BEST FIT MODEL FOR YIELD CURVE ESTIMATION - Zdravka Aljinović; Tea Poklepović; Kristina Katalinić (Croatian Operational Research Review, 2012)
Yield curve represents a relationship between the rate of return and maturity of certain securities. A range of activities on the market is determined by the abovementioned relationship; therefore its significance is unquestionable. Besides that, its shape reflects the shape of the economy, i.e. it can predict recession. These are the reasons why it is very important to properly and accurately estimate the yield curve. There are various models evolved for its estimation; however the most used are parametric models: Nelson-Siegel model and Svensson model. In this paper the yield curves are estimated on Croatian financial market, based on weekly data in years 2011 and 2012 both with Nelson-Siegel and Svensson model, and the obtained results are compared.